PENERAPAN MODEL INKUIRI TERBIMBING BERBASIS PENDEKATAN KONSTRUKTIVISME UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR KOGNITIF DI KELAS VIII.1 SMPN 4 KOTA BENGKULU - Monita Mialisa; Connie Connie; Rosane Medriati (Kumparan Fisika, 2017)
This study aims to determine the improvement of science process skills, learning activities and cognitive learning outcomes of students by applying a model of Guided Inquiry based on Constructivism Approach to the concept of Light in class VIII.1 SMPN 4 Kota Bengkulu. This research was conducted in four stages: planning, action implementation, observation, and reflection. The results showed that students' science skill score included observation indicator 63,8 (cycle I), 80,9 (cycle II), 82,1 (cycle III), 86,4 (cycle IV), indicator formulated hypothesis 44,8 (Cycle I), 60.3 (cycle II), 61.4 (cycle III), 78.6 (cycle IV), classification indicator 84 (cycle I), 89.2 (cycle II), 96, 2 (cycle III), 100 (cycle IV), interpreting indicators of 65.5 (cycle I), 67.6 (cycle II), 71.4 (cycle III), 77.1 (cycle IV), and communicator indicator Of 46.6 (cycle I), 63.5 (cycle II), 81.7 (cycle III), 90.9 (cycle IV). Student learning activity with cycle I average score 29,5 (enough), cycle II 32 (good), cycle III 34 (good) and cycle IV 37 (good). The results of cognitive learning obtained the average grade grade cognitive and classic learning completeness in the first cycle of 68.4 (enough) and 55.2% (unfinished), cycle II 79.5 (good) and 70.6% (not yet Thoroughly), cycle III 83 (good) and 77,1% (complete), cycle IV 85,4 (good) and 85,7% (complete). Based on the result of the research, it can be concluded that the implementation of Guided Inquiry Model Based on Constructivism Approach can improve the skill of science process, learning activity and student cognitive learning result.